Kapabilitas Dinamis Sebagai Penentu Dalam Mengadopsi Penerapan Bisnis Berbasis Teknologi Digital - Utomo, Mohamad Nur; Pratiwi, Sulistya Rini; Windani, Sakina Suci (Jurnal Nusantara Aplikasi Manajemen Bisnis, 2024)
Research aim: This research aims to analyze the influence of dynamic capabilities on the adoption of technology-based digital business applications in Small and Medium Enterprises (SMEs). Method: The study collected primary data through field studies in North Kalimantan, involving 73 SMEs using digital platforms, and analyzed it using Partial Least Squares - Structural Equation Modeling (PLS-SEM). Finding: Sensing, learning, and integrating capabilities positively impact the use of digital business tools, while coordinating capability doesn't seem to have a significant effect. Sensing involves watching market changes, leading to more digital marketing and customer reach. Learning drives gathering and using information for product improvement, increasing digital tool usage. Integrating fosters teamwork, aiding in digital tool adoption for better coordination. However, coordinating capability doesn't heavily affect digital tool usage, possibly due to SMEs' smaller scale. Theoretical contribution/Originality: This study supports the Resource-Based View (RBV) theory, emphasizing that dynamic capabilities help firms adjust resources to changing business landscapes, highlighting the significance of sensing, learning, and integrating capabilities for SMEs to effectively adopt technology-based digital business applications. Practitioner/Policy implication: SMEs intending to embrace digital business strategies should focus on enhancing dynamic capabilities, especially in sensing, learning, and integrating, to minimize conflicts and failures in technology adoption and ensure adaptability in dynamic business settings. Research limitation: The study encountered sample size limitations because of SMEs' hesitance to participate, potentially worsened by post-pandemic recovery activities.